Educational Comic-Based Digital Media to Increase Reading Interest of Elementary School Students - Siti Habibah Umairoh; Nurrohmatul Amaliyah (Jurnal Ilmiah Pendidikan Profesi Guru, 2022)
More effort is needed to become an integral person, one of which is through education. Where government policies are needed in realizing education that is relevant and continues to grow following the times. This study aims to develop educational comic-based learning media to increase students' reading interest. This type of research uses the Research and Development (R&D) method, with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The research subjects were third grade students in elementary school. Research data obtained through observation, questionnaires, and validity. The data obtained and analyzed using quantitative data. The answer is then measured using a Likert scale in the form of a checklist with a scale of five. Based on the results of the study, digital media has become a more practical and accessible place for learning, making the learning experience of students more natural and increasing activities and interests. The results of the validity of each material expert, media expert and linguist, indicate that digital media based on educational comics is very feasible for alternative media for students to increase interest in reading.